(untitled) (مجلة إحالات, 2026)
The corona epidemic is one of the most dangerous epidemics that have afflicted humanity in this era ; and the corona crisis has raised questions of existential anxiety ; where is this express train taking us? What will happen for humanity due to these sudden transformations ? Accordingly ; this research paper attemps to reveal the socio-psychological representations of the epidemic and the ontological interactions in a poem « Only ten possibilities » by the poet Mohammed Amine Saidi.